Análisis del sector cacaotero desde los aspectos de la competitividad sistémica, y su inserción en el mercado mundial (2017)
This paper analyzes the systemic competitiveness of the Colombian cocoa sector and the business opportunity that means its insertion in the international market, which begins with an exploration phase, in which the cocoa sector is contextualized, starting from the general to the particular , seeing both aspects of cocoa itself and the world market, producers and consumers of cocoa in the world, ending with the Colombian cocoa sector itself. Later a theoretical framework is made referring to the systemic competitiveness, which includes the description of each one of the levels to analyze (meta, macro, meso, micro) that allow an analysis regarding the competitive behavior of a sector in this case the cocoa and thus establish the international perspectives of it.